Effects of relaxation time and zero shear viscosity on structural evolution of linear low‐density polyethylene in shear flow. Issue 13 (27th November 2017) - Li, Kun; Matsuba, Go
ABSTRACT: The purpose of this work is to investigate the precursor formation and crystallization of four different types of linear low‐density polyethylene in shear flow. The aggregation of string‐like structure (precursor) in micrometer scale was observed by polarized optical microscopy. Although the existence of precursors accelerates crystallization, we find that it is unnecessary for the polymer fluid to possess crystalline structures at relatively high temperatures by wide‐angle X‐ray diffraction. The rotational rheometer result suggests that relaxation time is consistent with processes of the precursor formation observed at 120 °C, while zero shear viscosity affects the boundaries of their corresponding processing windows. According to these results, we propose a mechanism that the precursor formation consists of entanglement and relaxation stages. Entanglements preserve the ordered state of polymer chains, while they return to the initially disordered state during the relaxation stage. Under shearing, the polymer chain is oriented along the flow direction, and the degree of chain motion remains limited because the oriented parts are confined by the entanglements (characterized by zero shear viscosity η0 ) acting as slip‐links. However, some chain motions and relaxation (characterized by terminal relaxation time τ) can still take place during this stage. Afterwards, the polymer chain becomes disordered and some entanglements disappear. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46053. Abstract :